Fcγ Receptor IIA H/R131 Polymorphism in Patients with Antiphospholipid Antibodies - Atsumi, Tatsuya; Caliz, Rafael; Amengual, Olga; Khamashta, Munther A.; Hughes, Graham R. V. (Thrombosis and Haemostasis, 1998)
A role for Fcγ receptor in the pathophysiology of thrombosis in APS has been hypothesized. The polymorphism of this receptor, FcγRIIA H/R131, is associated with the binding affinity for human IgG2 (i.e. FcγRIIA-H131 isoform has a higher affinity than FcγRIIA-R131). Since anti-β2 glycoprotein I antibodies (anti β2GPI), which play a major pathogenic role in APS, show IgG2 dominant distribution, we investigated the prevalence of receptor isoforms in patients with anti-phospholipid antibodies (aPL) by a PCR-RFLP method. We studied 100 Caucasian patients with aPL (57 primary APS, 32 secondary APS to SLE and 11 other diseases with aPL) and 41 healthy controls. H131/H131, H131/R131 and R131/R131 genotypes were found in 21 (21%), 50 (50%) and 29 (29%) in the patient group, and 9 (22%), 23 (56%) and 9 (22%) in control group, respectively. Thus there was no statistically significant difference in the prevalence of each genotype in these groups. None of the clinical manifestations of primary APS (arterial/venous thrombosis, recurrent pregnancy loss and thrombocytopenia) was significantly correlated with any FcγRIIA genotype. In conclusion, FcγRIIA polymorphism did not correlate with the manifestations of APS, and FcγRIIA genotype is not a genetic marker of APS.